Spinal Cord Studies in the African Giant Rat (Cricetomys gambianus, Waterhouse) (Nigerian Journal of Physiological Sciences, 2021)
Summary: The African giant rat, AGR, is known for advantageous behavioural patterns among which are cognition and dexterous locomotion. This study investigated the morphological, morphometric and possible functional aspects of the AGR spinal cord (SC) anatomy. Ten adult (5 males and 5 females) AGR were used to determine the gross and histological features of the SC which were typically of rodent features. The mean SC weight and length given as 2.50±0.24g and 15.87±0.24cm respectively for the male and 2.32±0.16g and 15.40±0.61cm for the female showed no sexual dimorphism (p